Pediatric aspects of therapeutic drug monitoring of mycophenolic acid in renal transplantation - Tönshoff, Burkhard; David-Neto, Elias; Ettenger, Robert; Filler, Guido; Gelder, Teun van; Goebel, Jens; Kuypers, Dirk R. J.; Tsai, Eileen; Vinks, Alexander A.; Weber, Lutz T.; Zimmerhackl, Lothar Bernd (Transplantation reviews, 2011)
Mycophenolate mofetil (MMF) is widely used for maintenance immunosuppressive therapy in pediatric renal and heart transplant recipients. Children undergo developmental changes (ontogeny) of drug disposition, which may affect drug metabolism of the active compound mycophenolic acid (MPA). Therefore, a detailed characterization of MPA pharmacokinetics and pharmacodynamics in this patient population is required. In general, the overall efficacy and tolerability of MMF in pediatric patients appear to be comparable with those in adults, except for a higher prevalence of gastrointestinal adverse effects in children younger than 6 years. The currently recommended dose in pediatric patients with concomitant cyclosporine is 1200 mg/m2 per day in 2 divided doses; the recommended MMF dose with concomitant tacrolimus or without a concurrent calcineurin inhibitor is 900 mg/m2 per day in 2 divided doses. Recent data suggest that fixed MMF dosing results in MPA underexposure (MPA-area under the concentration-time curve (AUC0-12), <30 mg × h/L) early posttransplant in approximately 60% of patients. To achieve adequate MPA exposure in most patients, an initial MMF dose of 1800 mg/m2 per day with concomitant cyclosporine and 1200 mg/m2 per day with concomitant tacrolimus for the first 2 to 4 weeks posttransplant has been suggested. As in adults, there is an approximately 10-fold variability in dose-normalized MPA-AUC0-12 values between pediatric patients after renal transplantation, strengthening the argument for concentration-controlled dosing of the drug. Although the clinical utility of therapeutic drug monitoring of MPA for graft outcome and patient survival is still controversial, potential indications are the avoidance of underimmunosuppression, particularly in patients with high immunologic risk in the initial period posttransplant, in patients who are treated with protocols that explore the possibilities of calcineurin inhibitor minimization, withdrawal or even complete avoidance, and steroid withdrawal or avoidance regimens that might also benefit from intensified therapeutic drug monitoring of MPA. An additional indication especially in adolescent patients is the monitoring of drug adherence. Therapeutic drug monitoring of MPA in pediatric solid organ transplantation using limited sampling strategies is preferable over drug dosing based on trough level monitoring only. Several validated pediatric limited sampling strategies are available. Clearly, more research is required to determine whether pediatric patients will benefit from therapeutic drug monitoring of MPA for long-term maintenance immunosuppression with MMF.